2020
DOI: 10.1017/cjn.2020.257
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Age-Specific Trends in Acute Stroke Incidence: A 15-Year Population-Based Study of Administrative Data in Ontario, Canada

Abstract: Background: Contemporary data on temporal trends in acute stroke incidence, specific to stroke type and age, are lacking. We sought to evaluate temporal trends in incidence of ischemic stroke and intracerebral hemorrhage over 15 years in a large population. Methods: We used linked administrative data to identify all emergency department visits and hospital admissions for first-ever ischemic stroke or intracerebral hemorrhage in Ontario, Canada from 2003–2017. We evaluated annual age-/sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 20 publications
3
24
0
Order By: Relevance
“…According to the Global Burden of Disease Study, a significant increase in stroke prevalence and incidence rates in terms of ischemic stroke (IS) was found in both men and women aged under 70 years between 1990 and 2019, with even faster increases observed from 2010 to 2019 [ 1 ]. A stable or increasing trend in stroke incidence among middle-aged people was recently observed in the USA, Canada, Australia, and European countries including France [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Several studies have predicted a substantial increase in the number of stroke cases in high-income countries by 2030 and 2050, associated with almost a doubling of healthcare costs related to stroke by then [ 1 , 11 , 12 , 13 ], as supported by projections from the Dijon Stroke Registry for France [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the Global Burden of Disease Study, a significant increase in stroke prevalence and incidence rates in terms of ischemic stroke (IS) was found in both men and women aged under 70 years between 1990 and 2019, with even faster increases observed from 2010 to 2019 [ 1 ]. A stable or increasing trend in stroke incidence among middle-aged people was recently observed in the USA, Canada, Australia, and European countries including France [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Several studies have predicted a substantial increase in the number of stroke cases in high-income countries by 2030 and 2050, associated with almost a doubling of healthcare costs related to stroke by then [ 1 , 11 , 12 , 13 ], as supported by projections from the Dijon Stroke Registry for France [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…22 A decline in stroke incidence has also been observed in high-income countries, 2 which is consistent with the findings of this study: age-standardised incidence rate of ischaemic stroke decreased from 1990 to 2014 in Scotland, 23 decreased from 2003 to 2013 in Iran, 4 decreased from 2005 to 2018 in Denmark, 24 and showed a declining trend from 2003 to 2011, then increased until 2017 in Canada. 25 In this study, the incidence rate by age group showed a decreasing trend in men over the age of 60, and women over the age of 40, while showing a stable trend in the younger age groups. According to the Netherlands national registries, ischaemic stroke incidences of ages 18-49 years increased from 1998 to 2010, and the increase was greater in those of 18-39 years of age.…”
Section: Discussionmentioning
confidence: 46%
“…22 A decline in stroke incidence has also been observed in high-income countries, 2 which is consistent with the findings of this study: age-standardised incidence rate of ischaemic stroke decreased from 1990 to 2014 in Scotland, 23 decreased from 2003 to 2013 in Iran, 4 decreased from 2005 to 2018 in Denmark, 24 and showed a declining trend from 2003 to 2011, then increased until 2017 in Canada. 25 …”
Section: Discussionmentioning
confidence: 99%
“… 22 23 Our crude rates of ischaemic stroke and intracerebral haemorrhage during 2015–2017 were approximately 1.5–2 times the age- and sex-standardised rates during the same period in a previous study in Ontario. 24 However, that study included only the first-ever episode whereas we included episodes occurring after a 365-day period.…”
Section: Discussionmentioning
confidence: 99%